Reverse Takotsubo Cardiomyopathy in the Setting of Acute Asthma Exacerbation - Khan, Muhammad A (Cureus, 2021)
Takotsubo cardiomyopathy (TTC) is a reversible form of myocardial injury characterized by transient systolic and diastolic dysfunction secondary to regional left ventricle (LV) wall motion abnormalities. We present a case of a rare variant of TTC, termed reverse TTC (rTTC), involving basal hypokinesis with apical hyperkinesis accounting for less than 5% of identified cases of TTC. Our patient is a 49-year-old Hispanic female who presented for evaluation of dyspnea. She was diagnosed with acute asthma exacerbation. The patient admitted to more frequent use of her albuterol rescue inhaler. Over the course of her hospitalization the patient had elevation of Troponin I and underwent an echocardiogram and coronary angiogram, which revealed the diagnosis of rTTC in the setting of inhaled beta agonist overuse for acute asthma exacerbation. Our case highlights the importance of adequately managing asthma to prevent exacerbation and overuse of inhaled sympathomimetic agents in an effort to decrease the incidence of TTC in the asthmatic population.